(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article examines the psychological developmental characteristics of individuals with speech disorders. The main goals of correction, as well as methods and approaches aimed at psychological and speech therapy, are explained in detail.